Detection of Habitat Shifts of Cetacean Species: A Comparison Between 2010 and 2017 Habitat Suitability Conditions in the Northwest Atlantic Ocean - Chavez-Rosales, Samuel; Josephson, Elizabeth; Palka, Debra; Garrison, Lance (Frontiers in Marine Science, 2022)
The simultaneous effects of human activities in the ocean and climate change have already produced a series of responses from the marine ecosystems. With the potential increment of future human activities, such as offshore renewable energy developments, proactive management is required. To facilitate effective management and conservation actions, it is imperative to identify species potentially at risk and their critical habitats. Here we examine 16 cetacean species habitat suitability in the western North Atlantic Ocean using generalized additive models developed from data collected by NOAA- Northeast and Southeast Fisheries Science Centers from 2010 to 2017. The models were based on observed species distribution as a function of 21 environmental covariates and compare species-specific core habitats between 2010 and 2017. We identified seasonal differences in patterns of habitat change across guilds and an average northward shift of 178 km across the study area. The effects of these shifts are still unknown, but for already stressed species, the contraction or displacement of their historical habitat could worsen their population status. Therefore, the imminent development of offshore regions, in addition to the effects of climate change emphasize the need of adaptively managing ecosystems on the face of multiple challenges.